Salvage Archaeology at the Marine Drive Project Site: Documenting the Legacies of the Indigenous-European Encounters at Osu- Ghana. - Darko-Yeboah, B. (University of Ghana, 2022)
This research investigates the legacies of trade along the coast of the Christiansborg Castle, Osu as a result of Indigenous-European interactions from the late sixteenth century to the present. Salvage archaeology being one of the main methods used, was conducted at the beachfront of Osu to rescue the material legacies associated with the early Osu people, the Trans-Atlantic Trade and the interactions that were on the verge of being destroyed due to the Marine Drive Tourism Investment Project. Historical sources, oral traditions and archival data were also used to complement the archaeological data to derive as much information on the subject as possible. The Marine Drive Project is a beachfront project intended by the Ghanaian government to plan and develop 241 acres of land, stretching from the Osu Klottey Lagoon (behind the Christiansburg Castle) to the Accra Community Centre. Osu became a fountainhead of Dutch mercantile interest and a major point of embarkation and disembarkation of cargo. This partly boosted the coastal trade and added a wide array of mainly European trade goods. The trade boom also attracted many ethnolinguistic groups to relocate to Osu. After the abolition of slavery in 1807 by the Danes, Osu’s commercial viability depreciated significantly. Despite this, it became the seat of government after independence and was used by Dr. Kwame Nkrumah. Archaeological and historical evidence also indicated that interaction between the Africans and Europeans at Osu impacted subsistence and several aspects of traditional cultural lifeways. This is evident in the areas of indigenous dress codes and cuisine while the Europeans embraced local cuisine and cultural ties. Western formal education and the use of European construction designs/materials such as glass windows superimposed on metal frames, asbestos, red bricks and metal hinges constituted technologies incorporated in traditional architecture. This paper therefore assesses the findings from three excavated trenches that were characterized by midden deposits of pre-European, early Osu materials and those of Dutch, Danish and British Trans-Atlantic trade and colonial interactions.
PhD. Archaeology and Heritage Studies
Keywords: Salvage Archaeology; Marine; Ghana; Indigenous-European Encounters